Legislar nuevas causas para el visto bueno, por las que el empleador puede dar por terminado el contrato de trabajo, dentro del art. 172 del código de trabajo - García Cabrera, José Joaquín (2015)
Labour law, is the essential part of society, it has to do with economic and productive, for such consideration, it is effectively and law, and is translated as such in a social duty, depending on the development and socio-economic balance. The contractual relationship in the workplace, is realized through the concert of wills that configure, in this case, an employer employer or employer and the worker as a partner or labor supply, which enables the relationship under the regulatory framework regime governing it. When conflicts occur within this relationship of subjects, subject to the determination of the standard, whichever is the figure in treatment that precisely seek a legal formula to resolve one way or another the problem is formulated, to the authorities competent. Legal mechanisms that serve to terminate the employment contract, and consequently the employment relationship have been reviewed and analyzed in the present research, however, emphasizes the institution Views Well he, being the main part of the problem, which were reactivated this institution to be studied thoroughly, with the sole purpose of finding solutions to conflicts that arise in the social reality of our country, in the work environment. The causes for which both the employer and the worker, determined were the legal provisions referred to in Articles 172 and 173, however as the matter of treatment, she went to the causes of approval for which the employer may terminate the employment contract, and consequently such a deeper study, for the successful conclusion of a legal reform proposal that allows harmony in the ever cited employment. It was possible to establish some causes proposed by the investigator, who served as an alternative solution to certain loopholes that in clear harmony with reality, were able to establish their feasibility, in the sense that the causes attributed to workers, are consistent with social reality and exactly harmonize with the circumstances that were determined in the problem set into consideration within the research project